Vehicle and Wheels Stability Defined Using Driving Envelope Protection Algorithm - Efremov, Denis; Hanis, Tomas; Klauco, Martin (IEEE transactions on intelligent transportation systems, 2024)
This paper introduces Model Predictive Control for Driving Envelope Protection (MPC for DEP), a novel strategy aimed at enhancing vehicle stability derived from wheel limits, like locking, wheelspin, and skidding. Inspired by aerospace practices, MPC for DEP first defines stable maneuver boundaries based on vehicle controllability, ensuring the driver can control the vehicle's dynamics being inside the driving envelope. Utilizing model predictive control, this approach keeps the vehicle within predefined combined wheel slip limits, suitable for various vehicle configurations. This formulation is independent of friction properties. The paper presents a comprehensive control framework that integrates braking, acceleration, and steering actions while mirroring the driver's commands and confines to the driving envelope. Extensive experiments conducted using IPG CarMaker validate the controller's performance in scenarios such as sine with dwell, slippery surface acceleration, and braking while cornering with and without friction split pad. Results showcase the controller's robustness across diverse driving conditions, promising improved vehicle stability and safety. This work simplifies control architectures and sets the stage for safer and more stable vehicles.